1931
DOI: 10.1017/s0021859600009837
|View full text |Cite
|
Sign up to set email alerts
|

The Fungicidal Properties of Certain Spray-Fluids, VIII. The Fungicidal Properties of Mineral, Tar and Vegetable Oils

Abstract: The following substances proved fungicidal for the conidial stage of the hop mildew (Sphaerotheca Humuli):(1) Liquid paraffin at 2 per cent. emulsified with soft soap. The spray is harmless, or dangerous, to foliage according to the conditions (probably temperature) in the greenhouse.(2) Medicinal paraffin, emulsified with 0·75 per cent. castor-oil soap, is not quite fungicidal at 3 per cent.(3) “Summer solol”, a proprietary mineral-oil preparation containing 61·6 per cent. by weight high-boiling petroleum oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1933
1933
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Canola oils have been associated with reduced yield (Schneider andNorthover 1990, Pasini et al 1997), and are known to cause leaf burn if applied in full sun and/or above 30°C (Martin and Salmon 1931, Schneider and Northover 1990, Pasini et al 1997. Finger et al (2002) reported phytotoxicity when canola oil was applied at 8 L/ha, in areas on grapevine canopies where the oil pooled.…”
Section: Discussionmentioning
confidence: 99%
“…Canola oils have been associated with reduced yield (Schneider andNorthover 1990, Pasini et al 1997), and are known to cause leaf burn if applied in full sun and/or above 30°C (Martin and Salmon 1931, Schneider and Northover 1990, Pasini et al 1997. Finger et al (2002) reported phytotoxicity when canola oil was applied at 8 L/ha, in areas on grapevine canopies where the oil pooled.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the awareness of potentially adverse effects of pesticides, there is a need for the development of alternative methods to control crop diseases such as powdery mildews. Sodium carbonate (washing soda) has been used with success against powdery mildew in the early 1930s (Martin and Salmon, 1931). However, the method remained essentially unnoticed until the publication by Homma et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some plant oils emulsified with the same amount of soft soap, have been shown to be fungicidal against powdery mildew in the early 1930s (Martin and Salmon, 1930, 1931, 1933). These studies also remained essentially unnoticed until recent years when the interest of using plant oils for control of powdery mildew was revived (Northover and Schneider, 1993, 1996; Pasini, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of benzene to cyclohexane has resulted in a reduction of fungicidal and phytocidal properties, possibly associated with the loss of aromatic properties following hydrogenation. The correlation of foliage-injuring properties and aromatic character has already been illustrated by examples, given in Part VIII of this series (10), from the tar and petroleum oils and from the hydrogenation products of naphthalene. In that paper trials are recorded of dekalin which, at 2 per cent., with 0-5 per cent.…”
Section: The Fungicidal Properties Of Certain Spray-fluids XImentioning
confidence: 89%